Adaptive tracking control for quantized nonlinear systems via backstepping design technique. Issue 5 (March 2018) - Wang, Tong; Yu, Zhan; Li, Zhan
Abstract: In this paper, the adaptive tracking control problem for a class of strict-feedback nonlinear systems with quantized input signal is investigated. The hysteretic quantizer is introduced to avoid the chattering phenomenon and the backstepping method is used to design the controller. The tracking errors are guaranteed to be bounded in a small neighborhood of zero via appropriate design parameters. Finally, two simulation examples are given, and the simulation results further demonstrate the effectiveness of the proposed method.